Anti-inflammatory Activity of Tectona grandis Linn. F. Extract Against TNF-α using In Vivo and Silico Methods - Parawansah Parawansah; Nuralifah Nuralifah; Arfan Arfan; Sulastrianah Sulastrianah; Radja Al Fath Widya Iswara; Kiki Murni; Sitti Humairah (Jurnal Kefarmasian Indonesia, 2025)
Tumor necrosis factor-alpha (TNF-α), a cytokine involved in inflammation, plays a critical role in inflammatory processes, particularly in synovial cells. Therefore, TNF-α represents a promising target for anti-inflammatory interventions. This study investigates the anti-inflammatory potential of Tectona grandis leaf extract by evaluating its ability to inhibit TNF-α activity. To identify bioactive compounds from the extract that may interact with the TNF-α receptor, molecular docking simulations were employed. In vivo experiments were conducted using different doses of the extract (100, 200, and 300 mg/kg body weight), and TNF-α levels were quantified to assess the anti-inflammatory effect. At a dose of 300 mg/kg, TNF-α levels were significantly reduced to 0.358 μg/L, indicating superior anti-inflammatory activity compared to the lower doses (0.539 μg/L at 100 mg/kg and 0.433 μg/L at 200 mg/kg). Molecular docking simulations revealed two bioactive compounds, Phaeophorbid A and (132S, 17S, 18S)-132-Hydroxy-20-Chloro-Ethylpheophorbide A, which demonstrated strong binding affinities (-5.4 kcal/mol and -5.2 kcal/mol, respectively) and interacted with the TNF-α receptor through hydrogen bonds and hydrophobic interactions. These results underscore the potential of Tectona grandis as a source of novel anti-inflammatory agents, suggesting its value in the development of therapeutic strategies targeting TNF-α in inflammation-related disorders.